EFEKTIVITAS PERENCANAAN PAJAK: STUDI KASUS PT MIDI UTAMA INDONESIA TBK - Annisa Ayuningtyas; Ida Farida Adi Prawira; Memen Kustiawan (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
The tax expense of PT Midi Utama Indonesia increased in 2024, indicating fiscal inefficiency and the need for evaluation through tax planning. This study aims to formulate tax planning strategies in accordance with tax regulations. A descriptive qualitative method is employed using secondary data from the company’s 2024 annual report. The analysis identifies transactions that result in permanent and temporary differences requiring fiscal reconciliation and develops tax planning strategies based on tax-saving potential. The findings show that tax planning reduced income tax expenses by 6.5% in 2024 and 7.8% in 2023, while also increasing the company’s profit for the year, confirming tax planning as a legal and effective approach to improving fiscal efficiency.